2020
DOI: 10.3389/fmicb.2020.00716
|View full text |Cite
|
Sign up to set email alerts
|

Compositional and Quantitative Insights Into Bacterial and Archaeal Communities of South Pacific Deep-Sea Sponges (Demospongiae and Hexactinellida)

Abstract: In the present study, we profiled bacterial and archaeal communities from 13 phylogenetically diverse deep-sea sponge species (Demospongiae and Hexactinellida) from the South Pacific by 16S rRNA-gene amplicon sequencing. Additionally, the associated bacteria and archaea were quantified by real-time qPCR. Our results show that bacterial communities from the deep-sea sponges are mostly host-species specific similar to what has been observed for shallow-water demosponges. The archaeal deep-sea sponge community st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
52
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 80 publications
10
52
1
Order By: Relevance
“…Formerly placed within the Thaumarchaeota , the Crenarchaeota are well known and widespread sponge symbionts ( 48 51 ). Different genera have recently been observed in South Pacific Hexactinellida and Demospongiae ( 14 ). Nanoarchaeota and Patescibacteria also have recently been noticed as members of sponge microbial communities, including glass sponges, but no sponge-associated nanoarchaeal genome has been studied to date, and, likely due to their low abundance in other sponge species, patescibacterial genomes have not been studied in detail ( 14 , 52 , 53 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Formerly placed within the Thaumarchaeota , the Crenarchaeota are well known and widespread sponge symbionts ( 48 51 ). Different genera have recently been observed in South Pacific Hexactinellida and Demospongiae ( 14 ). Nanoarchaeota and Patescibacteria also have recently been noticed as members of sponge microbial communities, including glass sponges, but no sponge-associated nanoarchaeal genome has been studied to date, and, likely due to their low abundance in other sponge species, patescibacterial genomes have not been studied in detail ( 14 , 52 , 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, microorganisms have rarely been seen in glass sponges (12). However, a recent study of South Pacific sponge microbial communities has shown that general patterns seen previously in shallow-water sponge microbiomes, such as host specificity and low microbial abundance-high microbial abundance dichotomy, are generally applicable for these deep-sea sponge microbiomes as well, including those of glass sponges (14). Another study underlined the importance of ammonia-oxidizing archaea (family Nitrosopumilaceae, phylum Thaumarchaeota) in the deep-sea hexactinellid Lophophysema eversa using metagenomic data (15).…”
mentioning
confidence: 99%
“…Bacteria usually dominate sponge microbial communities, but archaea are regularly found in sponge hosts and can make up substantial parts of the community (e.g., 24% of the microbial community in the Great Barrier reef sponge Ianthella basta ) ( Moeller et al, 2019 ), and in some cases even dominate the communities (e.g., up to 63% in the microbial community of the sponge Axinella mexicana ) ( Preston et al, 1996 ). A comparison of the archaeal sponge community from hosts living in shallow waters and the deep-sea indicated that sponge-associated archaea appear to be much more abundant (up to three orders of magnitude greater) in the deep-sea ( Steinert et al, 2020 ). Most archaeal sponge symbionts are Thaumarchaeota, with some belonging to sponge-specific clades ( Simister et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…'metaorganism' (Bosch and McFall-Ngai 2011)) has been defined to cover the host plus its associated microbiota (Bordenstein and Theis 2015;Rohwer et al 2002). While the histology and trophic ecology of glass sponges has been a matter of several previous studies (Kahn and Leys 2017;Kahn et al 2018), the microbiology of glass sponges still remains largely unexplored (but see Steinert et al 2020;Tian et al 2016;Savoca et al 2019).…”
Section: Introductionmentioning
confidence: 99%